Rational engineering of yeast to develop biosensors - Cheng, Penghui (2015)
The yeast, Saccharomyces cerevisiae, is widely used to produce high value-added chemicals and food ingredients. Typically, genes are either deleted from or added to the yeast to produce a compound-of-interest. However, in doing so, we perturb cellular networks and affect the metabolism of the cell. It will be useful if we can readily determine the concentrations of various chemicals in the cell and dynamically regulate metabolic pathways, so that the cells can cope better. Thus, there is a need to develop biosensors for various chemicals for the yeast cells. [2nd Award]